1991
DOI: 10.1093/infdis/163.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged CD4+ Lymphocytopenia and Thrombocytopenia in a Chimpanzee Persistently Infected with Human Immunodeficiency Virus Type 1

Abstract: The immunologic and virologic status of a chimpanzee inoculated with multiple isolates of the human immunodeficiency virus type 1 (HIV-1) were assessed over 57 months to determine whether prolonged thrombocytopenia and CD4+ lymphocytopenia observed in the animal might be associated with long-term HIV infection. Although the chimpanzee showed no signs of disease, it lost both CD4+ (as low as 134 cells/microliter) and CD8+ lymphocytes approximately 30 months after initial infection, followed by thrombocytopenia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Except for the animal that developed AIDS [39,71], progressive decreases in CD4 ϩ T lymphocytes have not been reported in chronically infected HIV-positive chimpanzees [31,35]. In this study we identified 3 additional HIV-1-positive chimpanzees in the Yerkes cohort that have experienced profound reductions in both absolute numbers and percentages of CD4 ϩ T lymphocytes, similar to what has been described for human progressors [67-70, 72, 73, 112].…”
Section: Discussionsupporting
confidence: 68%
“…Except for the animal that developed AIDS [39,71], progressive decreases in CD4 ϩ T lymphocytes have not been reported in chronically infected HIV-positive chimpanzees [31,35]. In this study we identified 3 additional HIV-1-positive chimpanzees in the Yerkes cohort that have experienced profound reductions in both absolute numbers and percentages of CD4 ϩ T lymphocytes, similar to what has been described for human progressors [67-70, 72, 73, 112].…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, asymptomatic HIV-infected chimpanzees do not have anti-18-kD antibodies in their sera, although they were detected in one animal with profound lymphopenia [41].…”
Section: Anti-histone Antibodies In Hiv Infectionmentioning
confidence: 90%
“…The autoantibody was virtually absent in asymptomatic, HIV individuals, yet almost always detected in patients with ARC or AIDS. Further studies have indicated that the 18-kD antigen is a molecule which serologically resembles histone H2B (R. B. Stricker, unpublished observations), and in chimpanzees infected with HIV and macaques and mangabeys infected with simian immunodeficiency virus (SIV), the levels of anti-H2B antibodies in the serum proved to be a good indicator of clinical activity [12,13]. Recent biochemical analysis which involved N-terminal sequencing of the 18-kD antigen revealed complete amino acid homology with histone H2B (R. M. Comacchio et al, manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic relationships between human and simian immunodefi ciency viruses raised the possibility of a nonhuman primate origin of HIV-1 [ 23 ]. Investigators isolated strains from chimpanzees, the only other species susceptible to HIV-1 infection, which appeared to bear a close phylogenetic relationship to the human virus [ 24 ], and to a new strain of HIV-2 from a West African that was more closely related to one found in sooty mangabeys (SIV SM ) than to prototype human isolates. This work suggested that HIV-2 has been transmitted from monkey to human and is a member of closely related primate virus family.…”
Section: Historical Backgroundmentioning
confidence: 99%